2011
DOI: 10.1017/s0007114511004934
|View full text |Cite
|
Sign up to set email alerts
|

Oral inoculation of probioticsLactobacillus acidophilusNCFM suppresses tumour growth both in segmental orthotopic colon cancer and extra-intestinal tissue

Abstract: Modulation of the cellular response by the administration of probiotic bacteria may be an effective strategy for preventing or inhibiting tumour growth. We orally pre-inoculated mice with probiotics Lactobacillus acidophilus NCFM (La) for 14 d. Subcutaneous dorsal-flank tumours and segmental orthotopic colon cancers were implanted into mice using CT-26 murine colon adenocarcinoma cells. On day 28 after tumour initiation, the lamina propria of the colon, mesenteric lymph nodes (MLN) and spleen were harvested an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 45 publications
2
82
0
7
Order By: Relevance
“…It has been found that some probiotics could also retard the growth of tumor volume and enhance the apoptosis of tumor cells, but studies were mainly focused on colon tumors (41)(42)(43). Our results (Table 3) showed a significant antiproliferation and proapoptotic effect that correlates with suppression of 4NQO-induced oral cancer incidence by dietary L. salivarius REN are in line with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…It has been found that some probiotics could also retard the growth of tumor volume and enhance the apoptosis of tumor cells, but studies were mainly focused on colon tumors (41)(42)(43). Our results (Table 3) showed a significant antiproliferation and proapoptotic effect that correlates with suppression of 4NQO-induced oral cancer incidence by dietary L. salivarius REN are in line with these observations.…”
Section: Discussionsupporting
confidence: 89%
“…For this purpose, the present study evaluated the prophylactic and therapeutic effects of probiotics on patients with CRC in the pre-and postoperative, and at the same time searched for preventive strategies from recent experimental models. A large number of studies have shown that probiotics can prevent the initiation or development of cancer by changing the intestinal microbial composition, host protection against pathogenic bacteria and fungi, the production of biological substances such as short-chain fatty acid and conjugated linoleic acid, inactivation of carcinogenic compounds, improvement of gut barrier function, modulation of immune responses, apoptosis, anti-proliferative effects and antioxidant activity (21)(22)(23) (18) observed better outcomes by using these microorganisms in the therapeutic intervention for patients with CRC. Perioperative administration of probiotics reduces the inflammatory response, which can lead to a reduction in length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consumption of probiotic Lb. acidophilus NCFM resulted in the retardation of the growth of tumor volume and the enhancement of the apoptosis of tumor cells (Chen et al, 2012). The cells of this strain are reported to adhere to the HT-29 and Caco-2 cells derived from colon carcinoma (Goh and Klaenhammer, 2010).…”
Section: Introductionmentioning
confidence: 94%